REGULARITIES IN EVOLUTION OF JURASSIC FORAMINIFERS - Kuznetsova K.I. (My University, 2001)
The evolution of foraminifers during the Jurassic is considered in two aspects. The evolutionary aspect proper was analyzed using the internal biological features of these organisms and history of this faunal group was analyzed as depending on many factors that determine an intricate multicomponent evolutionary process, i.e., the compositional changes in assemblages, transformations related to habitat factors, spatial dispersion, etc. There are two main types of assemblages that differ in phylogeny and important parameters, such as the evolution rate at the species and generic levels, specialization degree, dominant species morphotypes, dimensions of adaptive areas, tolerance (ecological valence), and community structure with regard to constituent species and genera. The role of ecological factor and its influence on compositional transformation in foraminiferal communities of Jurassic seas in different climatic zones is analyzed.
Keywords: Jurassic; foraminifers; Mesozoic::Jurassic; Мезозой::Юрская